Dynamics of plankton populations as natural food for fish in a tributary of the Ogan River - Elva Dwi Harmilia; Khusnul Khotimah; Irkhamiawan Ma'ruf; Intan Pratiwi (Depik, 2022)
The research was conducted to determine the abundance, diversity, uniformity, and dominance of plankton in fish stomachs and waters that are expected to provide information about water productivity. The research was carried out in a tributary of the Ogan River, Indralaya District, Ogan Ilir Regency, South Sumatra at three stations, namely Indralaya Mulya Village, Tanjung Seteko Village and Muara Penimbung Village. The method used field surveys and location determination using purposive sampling with fish stomach contents, water samples for plankton observations, and water quality parameters. Fish sampling was carried out six times in 3 months, and water samples for plankton observations were one time per month, from April to June 2018. Plankton is found in fish stomachs and waters with a total abundance of 35.6 - 448.12 ind/l plankton consisting of 8 divisions with 11 classes. The plankton diversity index has moderate diversity and moderate community stability with a value between 1.11 - 1.45. The uniformity index of plankton in the fish stomach showed small uniformity of plankton (0.41-0.67), while in the waters, at station three and station 1 in April, the uniformity was high (E values 0.72 and E 0.93). The value of the plankton dominance index is in the range of 0.27-0.37. No species dominate other species or D = 0 (0.5), with moderately polluted water quality